The Path to Conserved Extended Haplotypes: Megabase-Length Haplotypes at High Population Frequency - Alper, Chester A. (Frontiers in Genetics, 2021)
This minireview describes the history of the conceptual development of conserved extended haplotypes (CEHs): megabase-length haplotypes that exist at high (≥0.5%) population frequency. My career began in internal medicine, shifted to pediatrics, and clinical practice changed to research. My research interest was initially in hematology: on plasma proteins, their metabolism, synthesis, and function. This narrowed to a focus on proteins of the human complement system, their role in immunity and their genetics, beginning with polymorphism and deficiency of C3. My group identified genetic polymorphisms and/or inherited deficiencies of C2, C4, C6, and C8. After defining glycine-rich beta glycoprotein as factor B (Bf) in the properdin system, we found that the genes for Bf (CFB), C2, C4A and C4B were inherited as a single haplotypic unit which we named the “complotype.” Complotypes are located within the major histocompatibility complex (MHC) between HLA-B and HLA-DRB1 and are designated (in arbitrary order) by their CFB, C2, C4A and C4B types. Pedigree analysis revealed long stretches (several megabases) of apparently fixed DNA within the MHC that we referred to as “extended haplotypes” (later as “CEHs”). About 10 to 12 common CEHs constitute at least 25 - 30% of MHC haplotypes among European Caucasian populations. These CEHs contain virtually all the most common markers of MHC-associated diseases. In the case of type 1 diabetes, we have proposed a purely genetic and epigenetic model (with a small number of Mendelian recessive disease genes) that explains all the puzzling features of the disease, including its rising incidence.